1990
DOI: 10.1021/bi00498a021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of 2-substituted derivatives of myristic acid to form potent inhibitors of myristoyl CoA:protein N-myristoyltransferase

Abstract: The importance of myristoylation for the proper biological functioning of many acylated proteins has generated interest in the enzymes of the myristoylation pathway and their interactions with substrates and inhibitors. Previous observations that S-(2-oxopentadecyl)-CoA, a nonhydrolyzable methylene-bridged analogue of myristoyl-CoA, was a potent inhibitor of myristoyl-CoA:protein N-myristoyltransferase (NMT) [Paige, L. A., Zheng, G.-q., DeFrees, S. A., Cassady, J. M., & Geahlen, R. L. (1989) J. Med. Chem. 32, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 23 publications
5
72
0
Order By: Relevance
“…We found that, like [ 3 H]myristate, the incorporation of azidomyristate into immunoprecipitated ctPAK2 was abolished in the presence of the NMT inhibitor HMA (19) (Fig. 3A), suggesting that the azidomyristate is recognized as a substrate by the highly selective NMT (5).…”
Section: Phosphine-biotin/flag-mediated Detection Of Azidomyristoylatmentioning
confidence: 92%
See 1 more Smart Citation
“…We found that, like [ 3 H]myristate, the incorporation of azidomyristate into immunoprecipitated ctPAK2 was abolished in the presence of the NMT inhibitor HMA (19) (Fig. 3A), suggesting that the azidomyristate is recognized as a substrate by the highly selective NMT (5).…”
Section: Phosphine-biotin/flag-mediated Detection Of Azidomyristoylatmentioning
confidence: 92%
“…3A), suggesting that the azidomyristate is recognized as a substrate by the highly selective NMT (5). Of note, when incorporated into cells, HMA is metabolically activated to 2-hydroxymyristoyl-CoA, a specific inhibitor of NMT that does not inhibit protein palmitoylation (17)(18)(19). While preventing the incorporation of [ 3 H]myristate or azidomyristate into ctPAK2 in cells induced to undergo apoptosis, HMA did not impair caspase 3-mediated PAK2 cleavage on STS treatment (data not shown).…”
Section: Phosphine-biotin/flag-mediated Detection Of Azidomyristoylatmentioning
confidence: 99%
“…3B). Furthermore, 2-hydroxymyristate, a known inhibitor of myristoylation (41,42), inhibits membrane localization of Fyn and Fyn (16)-eGFP to a greater extent than 2-bromopalmitate (Fig. 2B).…”
Section: -Bromopalmitate Inhibits Fyn Fatty Acylation In Cos-1mentioning
confidence: 97%
“…To determine whether protein N-myristoylation might be important for plant salt tolerance, we first tested the effect of HMA, a competitive inhibitor of N-myristoyltransferase (Paige et al, 1990;Nadler et al, 1993;Galbiati et al, 1996). One-week-old Arabidopsis seedlings were treated with 1 mM HMA for 1 day and then transferred to grow on a regular nutrient medium or on a medium supplemented with 100 mM NaCl.…”
Section: Mutant Phenotypementioning
confidence: 99%